Effects of group-based physical activity programs on children, adolescents, and young adults with disabilities: A systematic review - Jason D’Amours; Stéphanie Girard; Paule Miquelon; Pierre-Luc Veillette (PLoS ONE, 2025)
Purpose In recent years, a concerning decline in the physical activity levels of young individuals has been observed, with a notable impact on those with disabilities. Despite evidence suggesting that physical activity programs yield health benefits for youths with disabilities, there exists a significant gap in understanding the specific group-based effects, strategies for effectiveness, sustainability, program development, adaptation details, and empirical value. Method This systematic review examines quasi-experimental and experimental design research published from 2013 to 2025 on group-based physical activity programs for children, adolescents, and young adults (5–24 years old) with disabilities according to the PRISMA guidelines. Results The searches yielded 2 715 studies, of which 20 were included. This review highlights multiple disabilities, diverse program durations and activities, and favorable results spanning physical, social, emotional, and cognitive dimensions. The main findings indicated strategies for program effectiveness portrayed as adaptation details. Despite every study providing positive outcomes, limitation concerning confounding variables, sample size and disparity, generalizability, sustainability, and fidelity of implementation remain. Conclusions Overall, the selected studies suggest great holistic outcomes for youth with disabilities and are to be implemented in addition to special schools or treatment. Future research should explore differences among less common disabilities, emphasizing cognitive outcomes, trainer impact, and program inclusivity to develop accessibility and effective interventions for youth with disabilities.